The Historiography of Activity of Slobozhanshchyna Pedagogical Personalities – the Founders of the Medical and Pharmaceutical Education in Ukraine (19th – early 20th Сentury) - Lutaeva, Tetyana (Pedagogical Discourse, 2013)
The article is devoted to the historiography of pedagogical personalities’ activities – the founders of the national medical and pharmaceutical education in the 19th – early 20th century. Three historiographical stages of the study have been distinguish. It was noted that at the first stage (early 19th – early 20th centuries) analysis of the medical and pharmaceutical educatorʼs activity has been linked to the characteristic of University education that was under the influence of a great-power ideology, and at the second stage (the first quarter of the 20th century – the end of the 1980s) the new approaches to the evaluation of pedagogical personalities’ activity were searched under the rule of the communist ideology. It was proved that at the third stage (since 1991) the research of pedagogical personalities has been carried out at a new level, taking into account both the personal, social and scientific determinants.